Supplements with purported effects on muscle mass and strength - Valenzuela, Pedro L.; Morales, Javier S.; Emanuele, Enzo; Pareja-Galeano, Helios; Lucia, Alejandro (European journal of nutrition, 2019)
Purpose Several supplements are purported to promote muscle hypertrophy and strength gains in healthy subjects, or to prevent muscle wasting in atrophying situations (e.g., ageing or disuse periods). However, their effectiveness remains unclear. Methods This review summarizes the available evidence on the beneficial impacts of several popular supplements on muscle mass or strength. Results Among the supplements tested, nitrate and caffeine returned sufficient evidence supporting their acute beneficial effects on muscle strength, whereas the long-term consumption of creatine, protein and polyunsaturated fatty acids seems to consistently increase or preserve muscle mass and strength (evidence level A). On the other hand, mixed or unclear evidence was found for several popular supplements including branched-chain amino acids, adenosine triphosphate, citrulline, β-Hydroxy-β-methylbutyrate, minerals, most vitamins, phosphatidic acid or arginine (evidence level B), weak or scarce evidence was found for conjugated linoleic acid, glutamine, resveratrol, tribulus terrestris or ursolic acid (evidence level C), and no evidence was found for other supplements such as ornithine or α-ketoglutarate (evidence D). Of note, although most supplements appear to be safe when consumed at typical doses, some adverse events have been reported for some of them (e.g., caffeine, vitamins, α-ketoglutarate, tribulus terrestris , arginine) after large intakes, and there is insufficient evidence to determine the safety of many frequently used supplements (e.g., ornithine, conjugated linoleic acid, ursolic acid). Conclusion In summary, despite their popularity, there is little evidence supporting the use of most supplements, and some of them have been even proven ineffective or potentially associated with adverse effects.